Spin-orbit torque effective fields and spin accumulation in TA/CO/PT structure with in-plane magnetic anisotropy - Luo, Feilong (2018)
The magnetic recording technique of magnetoresistive random access and domain-wall memories requires a clear understanding of spin-orbit torque (SOT) which is applied for writing. In the writing unit where the structure of heavy metal (HM)/ferromagnetic metal (FM)/HM or oxide is commonly used, the SOT strength is represented by an effective field comprised of fieldlike and dampinglike terms. Generally, two distinct measurement approaches are used to characterize the effective field magnitude. In this thesis, a self-validating approach is proposed and demonstrated, which enables concurrent quantification of both the fieldlike and dampinglike terms in structures with in-plane magnetic anisotropy. Based on this method, in Ta/Co/Pt structure the dependences of the effective field on the thickness of Ta layer and the magnetization magnitude of Co layer are investigated. The investigation results reveal that the thickness of Ta varies the magnitude of the effective field. The fieldlike term decreases while the dampinglike term increases with the increase of the Co magnetization magnitude, indicating that the SOT effective field is tunable by the magnetization amplitude of FM layer. Angular dependence of the effective field is investigated. The results show that the fieldlike term consists of a component with fixed value and another component with azimuthal angle dependence, which experimentally supports that both Rashba and spin Hall effects contribute to the SOT. The dampinglike term is independent of the angle, indicating that the dampinglike term cannot be tuned by the azimuthal orientation of the magnetization. The SOT effective field, which has been characterized, is caused by spin accumulation in HM/FM interfaces. In this thesis, the spin accumulation is quantified by means of harmonic Hall resistance measurement. Spin accumulation up to 10% of the local magnetization is recorded when the applied electric current density is 10 to the power of 11 Amperes per square meter.